PENGARUH PROFITABILITAS, KEBIJAKAN DIVIDEN, DAN HUTANG TERHADAP NILAI PERUSAHAAN LQ 45 YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) 2014-2018 - Muhammad Syukron Salim; Noor Shodiq Askandar; Anik Malikah (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThis study aims to determine the effect of Profitability, Dividend Policy, and Debt to Company Value at Indonesian Company LQ 45 whose registered in the Indonesian Stock Exchange (BEI) for the 2014-2018 period, with purposive sampling technique for Indonesia Company LQ 45 in 2014-2018 and using multiple linear regression analysis with Statistical Package for the Social Sciences (SPSS), the data used is secondary data from the relevant resources. The results showed that the Profitability (ROA) has a significant positive effect on Company Value (PBV). Dividend Policy (DPR) has no effect on Company Value(PBV). Debt (DAR) has a significant positive effect on Company Value (PBV). This study is very useful for companies to increase the value of profitability ratios and debt to assets ratios because it can increase the value of the company. High corporate values wii increase investor confidence to invest and increase its shares, so that the company’s value can be maximum. Based on the conditions on previous studies, it still shows different results. Researcher are interested in developing this research using sectors as a research object.                 Keywords       : Profitability, Dividend Policy, Debt, Company Value